Hubungan Instrumen Pasar Keuangan Syariah dan Variabel Ekonomi Makro Terhadap Aset Keuangan Syariah - Nastiti, Hasna Mumtaz; Cupian, Cupian (Jurnal Ilmiah Ekonomi Islam, 2024)
The Islamic financial industry has an important role in supporting a sustainable economy, along with positive growth that can be seen from the development of its assets. One of the sectors, Islamic banking, also shows assets that grow significantly yearly. Islamic banking uses Islamic financial market instruments such as PUAS, FASBIS, and Sukuk to manage these assets. Therefore, this research wants to know the relationship of PUAS, FASBIS, and Sukuk to Islamic Banking assets and the influence of inflation and interest rate variables. By using a quantitative approach and secondary data processed by the VAR / VECM method, the results show that in the long term, PUAS, FASBIS, Sukuk, and BI Rate significantly influence Islamic banking assets. In the short term, only PUAS and Inflation significantly influence Islamic banking assets.